Territorial organization of tourism and recreation of metropolitan area of the Republic of Belarus - Zaitsau, Uladzimir M.; Reshetnikova, Anastasiya N.; Tryfanava, Iryna K. (Journal of the Belarusian State University. Geography and Geology, 2017)
The article describes the spatial-temporal laws of development of some of the most popular types of tourism and recreation within Minsk district – the metropolitan region of the Republic of Belarus. It shows the geographical, functional structure and dynamics of the spa facilities, the development features of rural tourism, and the analysis of territorial organization and dynamics of gardening partnerships as one of the most important segments of the suburban recreation. It is defined that in all of the studied types of tourist and recreational activities capital region is the leading region of the country by the number of tourists, and the dynamics of growth.This trend can be traced to the early 1990s and it has positive tendencies in the future. At the same time, taking into consideration the specifics of the resource potential, it is significantly differentiated on Minsk region territory. Based on current trends in the dynamics of tourism and recreational needs of the residents of the country, the age structure of its population and the level of urbanization, the need for rest is urban settlements will grow steadily.
Keywords: health tourism; recreation; sanatorium-resort business; agritourism; farm tourism estates; horticultural cooperatives